MDF-FACADE TECHNOLOGIES - Gayda, S.V. (Forestry, Forest, Paper and Woodworking Industry, 2018)
It is established that a worthy alternative to furniture facades made of natural wood are facades made of MDF materials: moldings and boards. The constructions are considered and the comparative analysis of constructions of three MDF facades is considered: MDF-Facade№1 for a hall frame-and-tile construction (a tile - a plate of MDF, bars - a MDF profile), a facade-MDF№2 for a hall frame-and-tile design (a tile) - MDF board, bars - solid wood), MDF-3 facade painted for the hallway (door base - MDF board). Modern materials for the creation of three versions of MDF facades with different structural elements and decor have been selected and calculated. A method of comparative research of technological processes of MDF facades with different components and components has been developed. Modern equipment for technological operations during the creation of MDF facades of the accepted type of research has been selected. The received equipment is calculated and the total cost for creation of three options of MDF facades is analyzed. Technological routes have been developed and plans of shops with selection of the accepted equipment for creation of three variants of MDF facades are constructed. The comparative analysis of technological processes is made and the rational variant on creation of front MDF facades of the accepted design is chosen. The payback period of investment costs for each option is calculated. It was found that the largest costs are for the second variant of the production process of MDF facades for hallways. The highest value of economic efficiency - the first option of investment. The payback period for this option is 0.41 years. Thus, it was established that the MDF facade of the frame-and-tile construction is rational and prestigious, and it is recommended for the introduction into production of technological solutions for its production for the assembly of furniture housings. In addition, the use of MDF facades in the range will give entrepreneurs the opportunity to produce quick-selling furniture products that meet the purpose, as well as aesthetic and design requirements.